Performance investigation of an advanced hybrid renewable energy system in Indonesia - Shezan, S.A.; Al-Mamoon, Abdullah; Hew, Wooi Ping (John Wiley & Sons, 2018)
The vast percentage of people of the world; particularly in the developing countries; are living mostly in the decentralized, rural and remote areas those are geographically secluded from the grid connection. Power distribution and continuous fuel transportation to produce the electrical energy for these areas pretenses a great challenge. Using renewable energy resources in off grid hybrid energy system might be a solution of this problem. Moreover, high cost of renewable energy systems has led to its slow adoption in many countries. Hence, it is vital to select an appropriate size of the system in order to reduce the cost and excess energy produced as well as to maximize the available resources. A hybrid energy system has been designed as well as simulated to support a small community considering an average load demand of 80 kWh/d with a peak load of 8.1 kW. The simulation and optimization of operations of the system have been done by HOMER software using the real time field data of solar radiation and average wind speed data of that area. The simulation ensures that the system is suitably feasible with respect to net present cost and CO2 emission reduction purpose. The result shows that NPC and CO2 emission can be reduced about 29.65% and 16 tons per year respectively compared with the conventional power plants. The NPC of the optimized system has been found about USD 160,626.00 having the per unit Cost of Energy about USD 0.431/kWh. The analyzed hybrid energy system might be applicable for other region of the world where the climate conditions are similar.